Determinants of agricultural companies’ firm value listed on the Indonesia Stock Exchange - Valencia Valencia; Hery Haryanto (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The goal of this study is to examine how firm size, corporate social responsibility, capital structure, profitability, and firm age impact the firm value of agricultural companies listed on the Indonesia Stock Exchange (IDX).Method — We employed the purposive sampling method to select a sample of 12 oil palm plantation companies listed on the Indonesia Stock Exchange (IDX) for the period between 2013 and 2021. The secondary data, comprising both quantitative and qualitative data, were collected from the websites of these sample companies. To analyze the collected sample, we utilized the panel regression analysis method by employing Stata 17 and SPSS (Statistical Product and Service Solutions) software.Result — We found that firm size had a significant and negative impact on firm value. However, corporate social responsibility, capital structure, profitability, and firm age did not show any significant impact on firm value.Contribution — This study contributes to the academic literature by examining oil palm plantation companies over a nine-year period and incorporating control variables such as profitability, firm size, and firm age.